The optimal performance target of valuation adjustment mechanism agreement with real options perspective - Yong Xue; Xinyi Yun (PLoS ONE, 2022)
The valuation adjustment mechanism (‘VAM’) agreement has recently been widely adopted in venture capital investment in emerging markets. The VAM agreement endows venture capital institutions a contractual right to reevaluate invested startup contingent on preset performance targets, which is crucial for the effectiveness of the VAM agreement by deeply affecting the strategy and fate of the startup. Motivated by exploring a rational performance target setting, this paper: 1)Firstly, extracts a general structure of the VAM agreement by cases analysis;2) Secondly, adopts a real options methodology to derive the option value held by venture capital institutions and how the pre-determined performance target affect the payoff of venture capital institutions;3)Thirdly, derives the expected time to achieve the given performance target and the behavior choice of entrepreneurs of startups; 4)Finally, by maximizing the contractual value of venture capital institutions with the participation constraints of the entrepreneur, derives the optimal performance target setting. The result finds that the option value of the VAM agreement is positively related to the performance target. It may partially explain why venture capital institutions tend to dominate overly high targets from a real options perspective. We also confirm the incentive effect of the VAM agreement that entrepreneurs tend to exert their best effort. Furthermore, the derivation of the optimal performance target shows that it is an increased function of the agreement period and a subtractive function of project risk. This paper contributes to the literature on contingent payment mechanisms and provides practical implications for the VAM agreement design.